Modulation of the thiol redox proteome by sugarcane ash-derived silica nanoparticles: insights into chronic kidney disease of unknown etiology - Arthur D. Stem; Cole R. Michel; Peter S. Harris; Keegan L. Rogers; Matthew Gibb; Carlos A. Roncal-Jimenez; Richard Reisdorph; Richard J. Johnson; James R. Roede; Kristofer S. Fritz; Jared M. Brown (Particle and Fibre Toxicology)
Abstract Introduction Chronic kidney disease of unknown etiology (CKDu) is an epidemic which is increasingly prevalent among agricultural workers and nearby communities, particularly those involved in the harvest of sugarcane. While CKDu is likely multifactorial, occupational exposure to silica nanoparticles (SiNPs), a major constituent within sugarcane ash, has gained increased attention as a potential contributor. SiNPs have high potential for generation of reactive oxygen species (ROS), and their accumulation in kidney could result in oxidative stress induced kidney damage consistent with CKDu pathology. Methods In order to characterize the impact of sugarcane ash derived (SAD) SiNPs on human kidney proximal convoluted tubule (PCT) cells and identify potential mechanisms of toxicity, HK-2 cells were exposed to treatments of either pristine, manufactured, 200 nm SiNPs or SAD SiNPs and changes to cellular energy metabolism and redox state were determined. To determine how the cellular redox environment may influence PCT cell function and toxicity, the redox proteome was examined using cysteine-targeted click chemistry proteomics. Results Pristine, 200 nm SiNPs induced minimal changes to energy metabolism and proteomic profiles in vitro while treatment with SAD SiNPs resulted in mitochondrial membrane hyperpolarization, inhibited mitochondrial respiration, increased reactive oxygen species generation, and redox proteomic trends suggesting activation of aryl hydrocarbon receptor (AHR) and other signaling pathways with known roles in mitochondrial inhibition and CKD progression. Conclusion Results suggest that PCT cell exposure to SAD SiNPs could promote glycolytic and fibrotic shifts consistent with CKDu pathology via oxidative stress-mediated disruption of redox signaling pathways.